Governing Disinformation Through Preventive Digital Policing: Technology, Legitimacy, and Social Implications in Indonesia - Andhika Raka Nurizki; Chairul Muriman Setyabudi; Solikhah Yuliatiningtyas (GoAcademica Research & Publishing, 2026)
The rapid expansion of digital technologies and social media has intensified the spread of disinformation and hate speech, creating significant social and governance challenges. While existing studies largely focus on platform governance, algorithmic regulation, or coercive law enforcement, limited attention has been given to preventive digital policing as a form of technology-enabled social governance. This study examines how preventive digital policing is implemented by Indonesia’s Criminal Investigation Agency (Bareskrim Polri) in addressing disinformation and hate speech, with particular emphasis on legitimacy and public trust. Using an exploratory case study approach, this research relies on secondary data, including official institutional documents, policy reports, and peer-reviewed academic literature. The data were analyzed through thematic analysis to identify patterns in technological adoption, preventive strategies, and institutional challenges. The findings show that Indonesia’s digital policing strategy prioritizes early detection through open-source intelligence (OSINT), multi-platform monitoring, and basic artificial intelligence tools, combined with non-coercive interventions such as digital warnings, online mediation, and public education initiatives. These measures emphasize persuasion and early intervention rather than punitive enforcement. However, the study also identifies key challenges related to technological limitations, regulatory ambiguity, institutional capacity, and public perceptions of surveillance and control. The findings suggest that the effectiveness of preventive digital policing depends less on technological sophistication than on transparency, procedural fairness, and societal acceptance. This study contributes to the science and society literature by reconceptualizing digital policing against disinformation as a legitimacy-dependent preventive governance mechanism, highlighting the interaction between technology, state authority, and social trust in a Global South context.